Water Birth Trend: Is It Safer and More Comfortable for Mothers and Babies? - Tri Budi Rahayu (PT. Anagata Sembagi Education, 2025)
In recent years, water birth has become increasingly popular as a more natural and comfortable alternative to conventional methods. This method is believed to reduce pain, speed up the labor process, and provide greater emotional control for mothers. This study aims to explore mothers' subjective perceptions and experiences of water birth through a qualitative approach with phenomenological methods and literature studies. Informants consisted of mothers who underwent water birth, midwives, obstetricians, and health facility managers. Data were collected through in-depth interviews and focus group discussions, and were strengthened by analysis of international academic and policy literature. The results of the study indicate that although many mothers feel more comfortable and satisfied with the water birth experience, there is still a gap between perceptions of comfort and medical safety standards. In Indonesia, limited infrastructure, medical personnel training, and unequal access are major challenges. Therefore, water birth must be carried out with the support of adequate facilities, strict medical protocols, and comprehensive education for pregnant women. This study emphasizes the importance of an evidence-based approach to ensure the safety and effectiveness of this method in the maternal health care system